2013
DOI: 10.1002/lary.23753
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteatoma in cleft lip and palate: A population‐based follow‐up study of children after ventilation tubes

Abstract: Children with cleft conditions are at increased risk of developing cholesteatoma compared to other children who had one or two MEVTIs, although the overall rate of cholesteatoma is declining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
0
28
2
2
Order By: Relevance
“…Recently, Jackler et al [23] criticized the invagination theory in several respects. Their criticism was depending on observing the results of other studies and can be summarized in the following points: first, the occurrence of cholesteatoma was not reduced after cleft palate repair or insertion of ventilation tubes in cleft palate patients [31,32]. Second, observing healthy and well-functioning Eustachian tube in some cholesteatomatous ears.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jackler et al [23] criticized the invagination theory in several respects. Their criticism was depending on observing the results of other studies and can be summarized in the following points: first, the occurrence of cholesteatoma was not reduced after cleft palate repair or insertion of ventilation tubes in cleft palate patients [31,32]. Second, observing healthy and well-functioning Eustachian tube in some cholesteatomatous ears.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various types of complications, tympanosclerosis and otorrhea generally present transient but common sequelae following VTI [73,74], with other studies reported permanent perforations and cholesteatoma [73,75,76]. As for the occlusion of grommets, infection, and the presence of granulation tissue, the evidence was too limited and blurred to determine the direction of effects between VTI and adverse events in CLP children with OME.…”
Section: Vti Versus Non-vtimentioning
confidence: 99%
“…The development of the disease is quite uncommon, with a reported rate of approximately 1% in non-CLP children with VTI [73,87]. However, evidence has shown that the CLP children were at increased risk of developing cholesteatoma [66,73], with a higher rate of 0-6.9% within 12 years after VTI [16,23,58,62,66,67,73,80,88].…”
Section: Cholesteatomamentioning
confidence: 99%
See 1 more Smart Citation
“…First, other complications apart from resolution and recurrent OME could occur in the middle ear following the removal of the ventilation tube, such as chronic otitis media (COM) with persistent eardrum perforation and cholesteatoma [5][6][7][8]. For example, Phua et al found that the rate of persistent eardrum perforations in children with routine grommet insertion was approximately 9% [5].…”
mentioning
confidence: 97%